Fexofenadine Adsorption by Activated Charcoal Impregnated with Hydrogen Peroxide - Hassen, Jasim Humadi; Ferhan, Mohammad Singar; Ayfan, Abdalkareem Hamad (Iraqi Journal of Science, 2020)
The adsorption of fexofenadine drug by activated charcoal powder impregnated with hydrogen peroxide (IAC) to improve its surface properties was investigated. The investigation also aimed to assess the effect of the repeated dose in increasing the amount of the drug adsorbed. The powder activated charcoal was impregnated with H2O2 3%. The effects of pH of the solution, concentration of the drug and time of the reaction parameters were investigated by using UV-Vis spectroscopy. The IAC was brought in contact with the drug solution in different pH (2, 4, 7 and 9), drug concentrations (30, 60, 90 and 120 Âµg ml-1) and time (15, 30, 45 and 60 minutes). After each experiment, a repeated dose of IAC was introduced into the solution and the adsorption process was repeated. The results showed that the amounts of the drug adsorbed were decreased with increasing the pH and increased with increasing the concentration of solution and time of contact. The adsorption capacity was enhanced to about 70% after the addition of the repeated dose. The study showed a spectrum displacement toward the blue region (blue shift) for the drug supernatant in all experiment parameters, which was almost doubled when a repeated dose was added.